ANALISIS PERMINTAAN DAN PENAWARAN JAGUNG DI INDONESIA (STUDI PERMINTAAN JAGUNG UNTUK PANGAN DAN INPUT INDUSTRI PETERNAKAN UNGGAS) - Desweni, Selly Prima; Sentosa, Sri Ulfa; Idris, Idris (Program Studi Magister Ilmu Ekonomi, 2015)
This study aims to analyze (1) the effect of the price of corn, rice, and income per capita, against demand of corn consumption in Indonesia, (2) the effect of the price of corn, harvested area and the price of grain to supply maize in Indonesia, (3) the amount of poultry industry workers, poultry population, the price of poultry and poultry prices for corn demand for industrial inputs Indonesia. This research is descriptive and associative study. While the type of data is documentary data, the data source is a secondary data, from 1983 - 2012. This study uses analysis: a) the simultaneous equation models. Endogenous variables in this study corn consumption demand, and supply of corn, exogenous variable is the price of corn, per capita income, the price of rice, harvested area, the price of grain. b). multiple linear regression model where the endogenous variables are demand of corn in poultry industry inputs while the exogenous variables are the amount of poultry industry workers, poultry population, the price of poultry feed, poultry prices. The study concluded that (1) the price of corn and negative significant effect on the level of demand for corn for household consumption Indonesia, Partially no significant difference between the positive and per capita income to the level of demand for corn in Indonesia, the price of rice a significant and positive effect on total demand for corn for household consumption in Indonesia. (2) the price of corn significant and positive impact on deals in Indonesia corn, corn harvested area of significant and positive impact on the offer of corn, grain prices and a significant positive effect on maize offers in Indonesia. (3) the number of workers poultry industry and a significant positive effect on the demand for corn inputs for poultry industry in Indonesia, poultry population does not affect the demand for corn input to the poultry industry in Indonesia, the development of the poultry feed prices and a significant negative effect on the demand for inputs corn for poultry industry in Indonesia, the price of chicken positive and significant impact on the demand for corn inputs poultry industry in Indonesia. Keywords: demand consumption for corn, supply for corn, poultry farming industry